SCREENING POTENTIAL ANTIOXIDANT AND ANTIBACTERIAL ACTIVITIES OF PROTEIN HYDROLYSATES DERIVED FROM GERMINATED LABLAB BEAN, PIGEON PEA AND KIDNEY BEAN - Ketut Ratnayani; Indriani Wisnu Susanto Panjaitan; Ni Made Puspawati (Journal of Health Sciences and Medicine, 2017)
Abstract Protein hydrolysate contains a mixture of various lengths of short peptides chain and free amino acids that may excert biological activities. This research aims to screen potential antioxidant and antibacterial activities of protein hydrolysate produced from three kinds of germinated beans i.e. lablab bean (Lablab purpureus), pigeon pea (Cajanus cajan (L.) Millsp) and kidney bean (Phaseolus vulgaris) through enzymatic hydrolysis process. The steps of research included germination process of the beans prior to total protein isolation, enzymatic hydrolysis of total protein isolates using pancreatin enzyme, evaluation of in vitro antioxidant activity of the hydrolysates protein using DPPH (1,1-diphenyl-2-picryl hydrazyl) method, and antibaterial activity testing towards Eschericia coli and Staphyllococcus aureus bacteria. The results revealed that pancreatine enzyme was able to hydrolyse germinated protein of lablab bean, pigeon pea and kidney bean at the experiment condition applied with degree of hydrolysis 34.12%, 27.44%, and 30,93% respectively. It was also found that protein hydrolysates of lablab bean, pigeon pea, and kidney bean demonstrated antioxidant activity which percentage radical DPPH scavenging activity of 84.02%, 68.97% and 67.89 %. On the other hand, all of those protein hydrolysates did not show any antibacterial activity towards Eschericia coli and Staphyllococcus aureus bacteria.